2009
DOI: 10.1007/s00244-009-9434-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Behavioral Parameters as Toxicity Biomarkers: Fish Responses to Waterborne Cadmium

Abstract: The disruptive sublethal effects of heavy metals on behavioral parameters of fish as biomarkers of aquatic toxicity have been scarcely studied. We investigated the impact of exposure to sublethal waterborne cadmium on locomotory parameters of three freshwater teleosts: Cyprinus carpio as reference species, and Australoheros facetum (sin. Cichlasoma facetum) and Astyanax fasciatus, native to Pampean ecosystems in Argentina, using a noninvasive bioassay under laboratory conditions. Fish were successively transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…It is possible that the observed discrepancy in Cd effects on locomotory behavior could partially be due to the use of different parameters for final assessment of the hypoactive or hyperactive nature of behavioral alterations. For example, while activity index decreased in Cd-exposed A. facetum, an increase in swimming velocity was observed at the same time (Eissa et al, 2010).…”
Section: Description Of Aop For Growth Impairment By Cadmiummentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that the observed discrepancy in Cd effects on locomotory behavior could partially be due to the use of different parameters for final assessment of the hypoactive or hyperactive nature of behavioral alterations. For example, while activity index decreased in Cd-exposed A. facetum, an increase in swimming velocity was observed at the same time (Eissa et al, 2010).…”
Section: Description Of Aop For Growth Impairment By Cadmiummentioning
confidence: 96%
“…Hypoactivity in response to Cd exposure has been observed in common carp (Eissa et al, 2006) and in Astraloherus facetum, a fish native to Argentina (Eissa et al, 2010). However, induction of hyperactivity by Cd has also been reported, for example, for bluegill sunfish (Ellgaard et al, 1978), rainbow trout (Majewski and Giles, 1981) and Atlantic salmon (Peterson et al, 1983).…”
Section: Description Of Aop For Growth Impairment By Cadmiummentioning
confidence: 96%
“…This relationship formed the basis for the EPA's hardness-dependent criteria for dissolved copper in aquatic environments (EPA 1985). However, it has also been reported that aquatic organisms exposed to elevated levels of heavy metals can show a temporary increase in activity during the period of initial exposure (Eissa et al 2009). Therefore, the snails in the low hardness treatment groups may have shown temporarily elevated levels of activity following exposure to the copper treatments.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, heavy metals can cause a number of adverse effects, such as alterations in the communication between cells and in the interaction with intracellular signal transduction proteins, which may in turn lead to alterations in cell growth and differentiation (Goering et al 1995). More recently, it has been shown that sublethal Cd also causes important changes in the swimming activity of C. carpio in captivity (Eissa 2009;Eissa et al 2006Eissa et al , 2009Eissa et al , 2010.…”
mentioning
confidence: 96%